Pengaruh Rasio Limbah Lumpur IPAL Pabrik Minyak Sawit Dan Pelepah Kelapa Sawit Terhadap Analisa Proksimat Pada Pembuatan Briket - Zostria Hanijah; Elvi Yenie; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Briquettes are alternative solid fuels that require development in the manufacturing process. The purpose of this study was to determine the effect of the ratio of sludge to palm fronds and particle size in the manufacture of sludge briquettes. This research was carried out by the process of carbonization of sewage sludge at 550OC for 60 minutes and the utilization of palm oil as an adhesive. The variables used are 40, 60 and 80 mesh particle size and 90:10%, 80:20%, 70:30%, 60:40% and 50:50% of silt sludge waste ratio. Testing of briquette characteristics of oil palm sludge include moisture content, ash content, volatile matter, carbon content, calorific value, compressive strength and duration of flame. The results showed the best briquette quality obtained on briquettes with 60 mesh particle size with 50:50% ratio with the highest calorific value of 3752,74 cal/gr. The best flame briquette reaches 4.41 minutes in briquettes with a particle size of 80 mesh and a ratio of 50:50% while the best compressive strength reaches 0.0102 kg/cm2 in 80 mesh particle size. The difference in the size of the briquette particles showed an increasing tendency in briquette flame duration. Keywords: briquette, sludge, particle size, flame duration, compressive strength